2015
DOI: 10.1016/j.jvs.2014.07.091
|View full text |Cite
|
Sign up to set email alerts
|

Mortality benefits of different hemodialysis access types are age dependent

Abstract: AVF is superior to AVG and HC regardless of the patient's age, including in octogenarians. In contrast, the mortality benefit of AVG over HC may not apply to younger (18-48 years) or older (>89 years) age groups. All patients 18 to 48 years should receive AVF for dialysis access whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 31 publications
0
56
0
Order By: Relevance
“…The elderly have specific health care requirements, as they are at increased risk of comorbidities that may result in frailty and reduced physical and cognitive function; furthermore, they often face complex psychosocial, financial, and transportation issues [28]. The creation and use of a VA in elderly patients requires the complex integration of patient, biological and surgical factors because the VA type might be a key factor influencing their survival [2, 9, 22, 29]. Data from the ERA-EDTA registry show that the likelihood of being treated with an AVF was 20, 24 and 37 % lower in the three oldest patient age-groups (60–69, 70–79 and >80 years) when compared to patients aged 22–44 years [30].…”
Section: Va In Elderly Patients: Recent Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elderly have specific health care requirements, as they are at increased risk of comorbidities that may result in frailty and reduced physical and cognitive function; furthermore, they often face complex psychosocial, financial, and transportation issues [28]. The creation and use of a VA in elderly patients requires the complex integration of patient, biological and surgical factors because the VA type might be a key factor influencing their survival [2, 9, 22, 29]. Data from the ERA-EDTA registry show that the likelihood of being treated with an AVF was 20, 24 and 37 % lower in the three oldest patient age-groups (60–69, 70–79 and >80 years) when compared to patients aged 22–44 years [30].…”
Section: Va In Elderly Patients: Recent Findingsmentioning
confidence: 99%
“…In fact, VA planning in the elderly is different from that in younger patients, and the Fistula First Initiative may not be the preferred approach for older patients because of their reduced life expectancy and conflicting results after surgery [8]. Although AVF may be superior to arteriovenous graft (AVG) and central venous catheter (CVC) in all age groups, including the elderly, many elderly patients have a heavy burden of comorbidities and insufficient vasculature for fistula maturation, resulting in a reduced rate of AVF patency [9]. Patients over 65 years have a fistula failure rate double that of younger patients [10]; furthermore, many fistulas will never be used due to the competing risk of death before dialysis initiation in this group [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of patients with end-stage renal disease, spline modeling showed that hemodialysis access outcomes differed at an age cutoff of 89 years. 28 Similarly, spline modeling analyses may also be able to assist in determining a precise cutoff at which AAA repair becomes too risky to pursue. However, before such a study can be performed, the accepted costs and acceptable predicted risk value associated with AAA repair must be established and agreed upon.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who did not have valid values for this data item were dropped from the analysis. We retained patients who survived at least 90 days after initiation of HD, consistent with other USRDS survival analyses (13,15). Demographic data were analyzed using chi-square statistics for dichotomous variables and the Kruskal-Wallis equality-of-populations rank test for continuous variables.…”
Section: Methodsmentioning
confidence: 99%